Design And Simulation Of A Fuzzy Logic Based Circadian Smart Led Lighting System And Its Potential For Healthcare Facilities - perumal, Sivachandran R. (2022)
This proof-of-concept research introduces a fuzzy logic-based lighting control system design to illuminate indoor spaces using Light Emitting Diode (LED) lighting technology by replicating outdoor circadian lighting to building indoor spaces. Past research shows circadian lighting affects occupants’ well-being by dictating their sleep and wake patterns. Previous works on replicating outdoor lighting had designers using classical closed loop control architecture, which required extensive mathematical modelling of the system dynamics. Fuzzy logic-based control systems costs less, robust, portable, and easily applicable for complex non-linear control systems without the need for system modelling. A methodology of autonomous regulation of lighting Correlated Colour Temperature (CCT) and space illuminance (lux) is applied using a 7×5 fuzzy rules base matrix using Mamdani max-min compositional operation. The design was evaluated by simulating a small-scale prototype to analyse the controller’s performance. Simulation results show the system output matched outdoor chromaticity values and the deviation from blackbody curve was within ±0.003 range using CCT Duv check. The system performed at no overshoot (0.0%), rise time and steady state reached at 1st and 4th iteration, respectively. Potential application at hospital ward are discussed by correlating with healthcare’s practise and parameters which showed increased facility efficiencies. Future works may experiment with spectrometric sensors and real time applications.